2011
DOI: 10.1186/1471-230x-11-41
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography for predicting esophageal/gastric varices in children with biliary atresia

Abstract: BackgroundTransient elastography (TE) is an innovative, noninvasive technique to assess liver fibrosis by measuring liver stiffness in patients with chronic liver diseases. The purpose of this study has been to explore the accuracy of TE and clinical parameters in predicting the presence of esophageal/gastric varices in children with biliary atresia (BA) following portoenterostomy.MethodsPatients with BA status post portoenterostomy and normal children were recruited. Splenomegaly and presence of EV/GV were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 29 publications
2
78
2
Order By: Relevance
“…However, we wonder why some biliary atresia patients show many of the symptoms associated with portal hypertension despite having relatively good liver biochemistry results. The previously reported cutoff values for liver stiffness measurements using transient elastography for diagnosing esophageal varices (9.7-12.7 kPa) are lower than those found in adults [13,26,27,30]. Unfortunately, the current study could not assess patients who showed a discrepancy between liver fibrosis and portal hypertension because such patients were mostly excluded from the assessment of esophageal varices due to prior treatment for esophageal varices and hypersplenism.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…However, we wonder why some biliary atresia patients show many of the symptoms associated with portal hypertension despite having relatively good liver biochemistry results. The previously reported cutoff values for liver stiffness measurements using transient elastography for diagnosing esophageal varices (9.7-12.7 kPa) are lower than those found in adults [13,26,27,30]. Unfortunately, the current study could not assess patients who showed a discrepancy between liver fibrosis and portal hypertension because such patients were mostly excluded from the assessment of esophageal varices due to prior treatment for esophageal varices and hypersplenism.…”
Section: Discussioncontrasting
confidence: 66%
“…The noninvasive detection of esophageal varices in biliary atresia patients appears to be of great importance in clinical practice. Three reports have described liver stiffness measurements using transient elastography as good markers of the presence of esophageal varices (area under the curve = 0.88-0.92) in postsurgical biliary atresia patients [13,26,27]. The aspartate aminotransferase to platelet ratio index might also be able to diagnose the presence of esophageal varices in postsurgical biliary atresia patients, with reported areas under the curves of 0.87-0.88 [13,27].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The sensitivity (and specificity) of TE (using a cut-off value of 12.7 kPa) and APRI (using a cut-off value of 1.92) in predicting esophageal/gastric varices were 84% (77%) and 84% (83%), respectively [57].…”
Section: Correlation With Fibrosis Stage and Different Etiologiesmentioning
confidence: 97%
“…The study revealed that transient elastography may be an equally useful tool for predicting the presence of esophageal/gastric varices as physical examination and biochemical or hematological tests. The sensitivity and specificity of TE in this study were 84% and 74% respectively; however, the sensitivity and specificity of splenomegaly (clinical parameter which was also assessed in this research) were 92% and 85% [28]. The other studies focused on TE were presented by Honsawek et al The main goal of this research was apparently to distinguish if serum adiponectin, galectin-3, tissue growth factor, osteopontine or soluble receptor for advanced glycation end products (sRAGE) level might be responsible for liver fibrosis.…”
Section: Biliary Atresiamentioning
confidence: 78%